Operation, control and monitoring of PEM fuel cell system - Lee, De Li. (2010)
Complex modulation and control method are major challenges to the renewable energy sources such as PEM fuel cell. Conventional methods of controlling the Z-Source Inverter have been limited by the inefficient and high losses. Therefore, it compels researchers to provide sustainable solutions in reducing switching losses. Utilization of One-Cycle Control is one of the simplest and fastest response approaches to eliminate the increasing of switchings per carrier cycle. Batch tests were conducted to investigate the effect of One-Cycle Control on switching loss reduction. One-cycle control was built and tested with the Z-Source Inverter. This report will discuss on the different parts of One-cycle Control and the influence on the Z-Source Inverter. The observations of the waveforms and the numbers of switching were studied in relation to the behaviour of the One-Cycle Control. Results proved that One-Cycle Control is an effective method in reducing switching loss. One-Cycle control is able to control the shoot-through and boost voltage. In addition, future developments of the experiments on One-Cycle Control were elaborated at the end of the report.